2014
DOI: 10.1155/2014/471764
|View full text |Cite
|
Sign up to set email alerts
|

Optical Scattering Properties of Intralipid Phantom in Presence of Encapsulated Microbubbles

Abstract: In imaging, contrast agents are utilized to enhance sensitivity and specificity of diagnostic modalities. In ultrasound imaging, microbubbles (MBs)—a gas-core shell-encapsulated agent—are used clinically as contrast agents. The working hypothesis of this study is that microbubbles can be employed as an intravascular contrast agent in optical imaging systems. In this work, the interaction of light and microbubbles in a turbid medium (intralipid) was investigated, particularly, the effect of MBs on the reduced s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…The reduced scattering coefficient of the phantom was ∼7 cm −1 at 532 nm. 23,24 A CMOS camera was used to capture the illumination at both wavelengths. Then, we performed phantom experiments to characterize the PACT system with internal illumination.…”
Section: Methodsmentioning
confidence: 99%
“…The reduced scattering coefficient of the phantom was ∼7 cm −1 at 532 nm. 23,24 A CMOS camera was used to capture the illumination at both wavelengths. Then, we performed phantom experiments to characterize the PACT system with internal illumination.…”
Section: Methodsmentioning
confidence: 99%
“…17,18 In addition to the high resolution svOCT imaging of microvasculature, it has potential to provide new insight into the dynamics of vascular remodeling. [19][20][21] In our previous phantom study, 11 we demonstrated that MBs can be used as an optical contrast agent, yielding increased scattering (1.4× at 300 nm and 6× at 850 nm). Similarly, Barton et al 10 have shown that MBs enhanced the backscattered OCT signal in model scattering media.…”
Section: Introductionmentioning
confidence: 78%
“…8 In light of these drawbacks, microbubbles [MBs; currently Food and Drug Administration (FDA) approved intravascular contrast agents in diagnostic ultrasound 9 ] may have a role to play as OCT contrast agents. 10,11 MBs are micrometer sized shell-encapsulated gas-core spheres. They are considered intravascular agents, i.e., following intravenous injection, they remain within the blood compartment and do not extravasate.…”
Section: Introductionmentioning
confidence: 99%
“…A measurement series in an Intralipid phantom was done for comparison with literature. Four percent Intralipid (200 mg/mL, Fresenius Kabi, Sweden) was mixed in distilled water for 0.8% lipid in total and μs = 8 cm −1 , comparable with that used by He et al and Zhou et al . Measurements were made for five source‐detector fiber separations between 6 and 25 mm at 20°C.…”
Section: Methodsmentioning
confidence: 99%